Exploring Students Experience in Online Speaking Class Using Role-Play Technique - Riandy Arifputra Pradhana (Journal of English Language and Education, 2021)
This paper aims to described the experience of the students toward using role-playing technique as a tool to learn speaking in online class, as well as the benefits and difficulties of implementing role play technique in online speaking class. A narrative inquiry study uses as research design for this study and the research conducted in Senior High School 3 Cikampek, and there are four participants participating in this research. The data were collected through a semi-structured interview and analyzed through Robert Yin analysis data technique. The data then coded and read multiple times, and then presented in final written form. The result from this study indicated that, every participant had a good and enjoyable experience by using role play technique role. The study also found that every participant got some benefits by using this technique and also this study found that, there are some difficulties that the participants faced and experienced by using this technique.